Penyuluhan Etika Sosial Digital bagi Remaja Berbasis Kearifan Lokal Di Kota Mataram Nusatenggara Barat - Ahmad Fadli; Siti Nur Aisyah; Rian Hidayat; Dewi Lestari; Muhammad Arifin; Laila Khadijah; Nurul Hidayati (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2026)
The rapid development of digital technology has fundamentally transformed the social interaction patterns of Indonesian adolescents, generating various ethical challenges such as cyberbullying, hoax dissemination, hate speech, and privacy violations in digital spaces. This community service program aims to enhance adolescents' understanding and practice of digital social ethics by integrating local wisdom values as contextually relevant and meaningful moral foundations. Implementation employed a participatory learning approach through workshops, focus group discussions, peer education, and digital mentoring over four months, involving 220 senior and vocational high school students, 60 teachers, and 150 parents in Mataram City. Results demonstrated an 81% increase in digital ethics literacy, a 67% reduction in negative digital behaviors, and a 74% strengthening of local wisdom values in online interactions. The program successfully established school-based Digital Ethics Ambassador communities, whose sustainability is ensured through institutionalization in school policies and partnerships with local government.